2020
DOI: 10.1002/jnm.2765
|View full text |Cite
|
Sign up to set email alerts
|

Variable step size fractional incremental conductance for MPPT under changing atmospheric conditions

Abstract: This paper presents a new modified variable step size Fractional Order Incremental Conductance (FOIC) with maximum power point tracking using Fractional Order PID controller tuned by bio-inspired Particle Swarm Optimization (PSO) to find optimal gain values of fractional integrator order (λ) and fractional derivative order (μ). The classical incremental conductance and FOIC show drawbacks under changing irradiance, oscillation around maximum power point (MPP) which decreases its convergence speed. To resolve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…An MPPT algorithm guarantees that the PV generates the maximum power possible when solar radiation is available. 24 The proposed controller directs the battery to either absorb surplus power produced by the PV panel or to deliver the required power to the load. The key advantages and contributions of this paper are • The advantage is that Lyapunov's method is a general method for stability analysis and can also be used for linear control design for nonlinear plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An MPPT algorithm guarantees that the PV generates the maximum power possible when solar radiation is available. 24 The proposed controller directs the battery to either absorb surplus power produced by the PV panel or to deliver the required power to the load. The key advantages and contributions of this paper are • The advantage is that Lyapunov's method is a general method for stability analysis and can also be used for linear control design for nonlinear plants.…”
Section: Introductionmentioning
confidence: 99%
“…The BQZSDC is used to simultaneously manage the power of a PV source, battery, and load. An MPPT algorithm guarantees that the PV generates the maximum power possible when solar radiation is available 24 . The proposed controller directs the battery to either absorb surplus power produced by the PV panel or to deliver the required power to the load.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used conventional power point tracking techniques are illustrated as Perturb and Observe (P&O), 9 Fractional Short Circuit (FSC) current, 10 Fractional Open Circuit (FOC) voltage, 11 and Incremental Conductance (IC) 12 . In P&O, the present PV power is compared successfully with the already existed power in order to extract the maximum output power of the solar PV.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the P&O, in the IC technique, the instantaneous conductance is compared with the previously stored conductance. Based on the sign of comparative result, the conductance step size has been improved 12 . The design and implementation of FSC current and FOC voltage power point tracking methods are easy.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on this area has shown the chance of increasing PV systems with wind turbines with minimal adjustments. To consolidate the wind turbine and the PV in a hybrid system, [4] have utilized a converter of a three-phase square waveform. To work more on the DC loads of hybrid system, another three-input dc-dc boost converter is being presented in [40].…”
mentioning
confidence: 99%